Study guide to accompany McConnell and Brue : economics - Walstad, William B.; Bingham, Robert C. (Boston : McGraw-Hill, 1996)
Economics
Keywords: Economics; Market system; Global economy; Employment; Fiscal policy; Banking; Monetary policy; Macroeconomics; Microeconomics; Product market; Resource market; Economic problems; International economics; World economy